â€œIsnâ€™t Self-destruction Coded into Us, Programmed into Each Cell?â€: A Thanatological, Posthumanist Reading of Alex Garlandâ€™s Annihilation (2018) - Kosonen, Heidi (Journal of Ecohumanism, 2023)
As both a novel (VanderMeer, 2014) and cinematic adaptation (Garland, 2018), Annihilation has engaged posthumanist and ecocritical scholars seeking to answer to the demand for art forms to participate in the renegotiation of the grand narratives feeding the ongoing environmental crisis and chipping away at the liveability of Planet Earth. In my reading of Alex Garlandâ€™s film, I discuss how its depiction of death adds to these discussions by challenging the human exceptionalism built into meaning-making processes, which have situated humans as above â€œnature,â€ including death, by defining human life as more valuable than all other life. As an umbrella term covering these varied processes, I discuss biopower, which seeks to regulate life by forbidding death in humans and denying life to other kind of life forms. I locate Annihilation within films that make use of the cinematic mode of ecohorror, exploring human fears and anxieties relating to death and â€œmonstrous natureâ€ with an ecocritical twist. I employ film analysis and draw theoretically on thanatological and posthumanist discussions, as I reflect on the kind of understanding of death that arises in Annihilation and centre on the discussion of self-destruction and suicide in discussing the human character Josieâ€™s death in relation to the filmâ€™s non-human actant, The Shimmer.